Reconstruction of Paprosky III defects with custom-made implants: do we get them in the correct position?: short-term radiological results. (12th October 2022) - Wessling, Martin; Gebert, Carsten; Hakenes, Tilmann; Dudda, Marcel; Hardes, Jendrik; Frieler, Sven; Jeys, Lee M.; Hanusrichter, Yannik
Abstract : Aims: The aim of this study was to examine the implant accuracy of custom-made partial pelvis replacements (PPRs) in revision total hip arthroplasty (rTHA). Custom-made implants offer an option to achieve a reconstruction in cases with severe acetabular bone loss. By analyzing implant deviation in CT and radiograph imaging and correlating early clinical complications, we aimed to optimize the usage of custom-made implants. Methods: A consecutive series of 45 (2014 to 2019) PPRs for Paprosky III defects at rTHA were analyzed comparing the preoperative planning CT scans used to manufacture the implants with postoperative CT scans and radiographs. The anteversion (AV), inclination (IC), deviation from the preoperatively planned implant position, and deviation of the centre of rotation (COR) were explored. Early postoperative complications were recorded, and factors for malpositioning were sought. The mean follow-up was 30 months (SD 19; 6 to 74), with four patients lost to follow-up. Results: Mean CT defined discrepancy (Δ) between planned and achieved AV and IC was 4.5° (SD 3°; 0° to 12°) and 4° (SD 3.5°; 1° to 12°), respectively. Malpositioning (Δ > 10°) occurred in five hips (10.6%). Native COR reconstruction was planned in 42 cases (93%), and the mean 3D deviation vector was 15.5 mm (SD 8.5; 4 to 35). There was no significant influence in malpositioning found for femoral stem retention, surgical approach, or fixation method. Conclusion: At short-term follow-up, we found that PPR offers a viable solution for rTHA in cases with massive acetabular bone loss, as highly accurate positioning can be accomplished with meticulous planning, achieving anatomical reconstruction. Accuracy of achieved placement contributed to reduced complications with no injury to vital structures by screw fixation. Cite this article: Bone Joint J  2022;104-B(10):1110–1117.